Comparative analysis of nitrogen content and its influence on actinorhizal nodule and rhizospheric microorganism diversity in three Alnus species - Yuan, Yuwei; Chen, Zhi; Huang, Xin; Wang, Fang; Guo, Hongying; Huang, Zhen; Yang, Hanbo (Frontiers in Microbiology, 2023)
Alnus spp. (alder) are typical nonleguminous nitrogen-fixing trees that have a symbiotic relationship with Frankia. To explore the differences in nitrogen-fixing microorganisms between three alders (A. cremastogyne, A. glutinosa, and A. formosana) with different chromosome ploidies, the community structure and compositional diversity of potential nitrogen-fixing microorganism in root nodules and rhizosphere soil were comparatively analyzed using 16S rRNA and nitrogenase (nifH) gene sequencing. The nitrogen contents in the root nodules and rhizosphere soil were also determined. The results showed that the contents of total nitrogen and nitrate nitrogen in the root nodules of the three alders are significantly higher than those in the rhizosphere soils, while the ammonium nitrogen content show the opposite trend. The family, genus, and species levels showed obviously differences between root nodules and rhizosphere soils, while there were no significant differences at the classification level between the three alders. At the phylum level, the dominant phyla from 16S rRNA and nifH gene data in the root nodules and rhizosphere soil of the three alders are phylum Actinomycetota and phylum Pseudomonadota, respectively. The LEfSe results showed that there are significant differences in the dominant groups in the root nodules and rhizosphere oil of the three alders. The relative abundances of dominant groups also showed obvious differences between the root nodules and rhizosphere soils of three alders. The relative abundances of Frankia and unclassified_Frankia in root nodules are obviously higher than those in rhizosphere soils, and their relative abundances in A. glutinosa root nodules are significantly higher than those in A. cremastogyne and A. formosana at the genus and species levels. The diversity of potential nitrogen-fixing microorganism from 16S rRNA and nifH gene data in the A. glutinosa root nodules and rhizosphere soils are all higher than those in A. cremastogyne and A. formosana. The results of functional prediction also showed that the OTUs for nitrogen fixation, nitrate respiration, and ureolysis in A. glutinosa root nodules are higher than those in the other two alders. Redundancy analysis revealed that the total nitrogen content mostly affects the Frankia community. Overall, there are significant differences in the community composition and structure of potential nitrogen-fixing microorganism in the root nodules and rhizosphere soils between the three alders. A. glutinosa showed a relatively stronger nitrogen fixation capacity than A. formosana and A. cremastogyne. The results help elucidates how the community structure and nitrogen-fixing ability of potential nitrogen-fixing microorganism differ between alder species and serve as a reference for applying Frankia to alder plantations.